Plasma Electrolytic Oxidation as a Feasible Surface Treatment for Biomedical Applications: an in vivo study - Polo, Tárik Okon Braga [UNESP]; da Silva, William Phillip [UNESP]; Momesso, Gustavo Antonio Correa [UNESP]; Lima-Neto, Tiburtino José [UNESP]; Barbosa, Stéfany [UNESP]; Cordeiro, Jairo Matozinho; Hassumi, Jaqueline Suemi [UNESP]; da Cruz, Nilson Cristino [UNESP]; Okamoto, Roberta [UNESP]; Barão, Valentim A. R.; Faverani, Leonardo P. [UNESP] (Springer Nature, 2020)
Objectives: In this in vivo animal study, we evaluated the effect of plasma electrolytic oxidation (PEO) coating on the topographic and biological parameters of implants installed in rats with induced osteoporosis and low-quality bones. Materials and methods: In total 44 Wistar rats (Rattus novergicus), 6 months old, were submitted to ovariectomy (OXV group) and dummy surgery (SHAM group). After 90 days, the ELISA test was performed and the ovariectomy effectiveness was confirmed. In each tibial metaphysis, an implant with PEO coating containing Ca2+ and P5+ molecules were installed, and the other tibia received an implant with SLA acid etching and blasting (AC) (control surface). After 42 days, 16 rats from each group were euthanized, their tibias were removed for histological and immunohistochemical analysis (OPG, RANKL, OC and TRAP), as well as reverse torque biomechanics. Data were submitted to One-way ANOVA or Kruskal-Wallis tests, followed by a Tukey post-test; P < 0.05. Histological analyses showed higher bone neoformation values among the members of the PEO group, SHAM and OVX groups. Immunohistochemical analysis demonstrated equilibrium in all groups when comparing surfaces for TRAP, OC and RANKL (P > 0.05), whereas OPG showed higher PEO labeling in the OVX group (P < 0.05). Biomechanical analysis showed higher reverse torque values (N.cm) for PEO, irrespective of whether they were OVX or SHAM groups (P < 0.05). Conclusion: The results indicated that the PEO texturing method favored bone formation and showed higher bone maturation levels during later periods in osteoporotic rats.